2020
DOI: 10.1038/s41388-020-1341-1
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbiota modulation: a novel strategy for prevention and treatment of colorectal cancer

Abstract: Research about the role of gut microbiome in colorectal cancer (CRC) is a newly emerging field of study. Gut microbiota modulation, with the aim to reverse established microbial dysbiosis, is a novel strategy for prevention and treatment of CRC. Different strategies including probiotics, prebiotics, postbiotics, antibiotics, and fecal microbiota transplantation (FMT) have been employed. Although these strategies show promising results, mechanistically by correcting microbiota composition, modulating innate imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
288
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 386 publications
(323 citation statements)
references
References 150 publications
0
288
0
1
Order By: Relevance
“…Ruminococcaceae, Faecalibacterium, specifically Ruminococcae, Alistipes, and Eubacterium species (196) Renal cell carcinoma Ruminococcaceae, Faecalibacterium, specifically Ruminococcae, Alistipes, and Eubacterium species (196) immunotherapy, or even to conquer opposition-held by nonresponders. To our best information, no clinical preliminaries assessing gut microbiome control and treatment viability are distributed right now (201). A couple of clinical preliminaries are started and now at the selecting stage ( Table 4) in light of Fong et al (201).…”
Section: Effects On Cancer Immunotherapymentioning
confidence: 99%
See 1 more Smart Citation
“…Ruminococcaceae, Faecalibacterium, specifically Ruminococcae, Alistipes, and Eubacterium species (196) Renal cell carcinoma Ruminococcaceae, Faecalibacterium, specifically Ruminococcae, Alistipes, and Eubacterium species (196) immunotherapy, or even to conquer opposition-held by nonresponders. To our best information, no clinical preliminaries assessing gut microbiome control and treatment viability are distributed right now (201). A couple of clinical preliminaries are started and now at the selecting stage ( Table 4) in light of Fong et al (201).…”
Section: Effects On Cancer Immunotherapymentioning
confidence: 99%
“…To our best information, no clinical preliminaries assessing gut microbiome control and treatment viability are distributed right now (201). A couple of clinical preliminaries are started and now at the selecting stage ( Table 4) in light of Fong et al (201). It stays dark whether these preclinical discoveries can be effectively meant clinical application.…”
Section: Effects On Cancer Immunotherapymentioning
confidence: 99%
“…A recent randomized, double-blind, placebo-controlled trial (NCT03782428) revealed that treatment with six viable microorganisms of Lactobacillus and Bifidobacterium strains significantly reduced the levels of pro-inflammatory cytokines such as TNF-α, IL-6, IL-10, IL-12, IL-17A, IL-17C, and IL-22 and prevented post-surgical complications as well [ 127 ]. Probiotics are generally considered safe and well-tolerated for healthy subjects, but in patients with underlying medical conditions, their safety profile is uncertain [ 62 ]. Probiotic translocation, which refers to the entry of viable bacteria into extraintestinal sites, leads to the ensuing systemic or localized infections.…”
Section: Clinical Applications Of the Gut Microbiota Modulation Fomentioning
confidence: 99%
“…Indeed, various case reports of probiotic-associated bacteremia, endocarditis, liver abscess, and pneumonia have been published [ 128 ]. Nevertheless, another theoretical risk regarding long-term probiotic use is the possible transmission of antibiotic-resistant genes via horizontal gene transfer [ 62 ].…”
Section: Clinical Applications Of the Gut Microbiota Modulation Fomentioning
confidence: 99%
“…As a target for antibiotics action [153], it seems highly likely that diverse levels of microbiota dysbiosis may boost the negative effects of antibiotic exposure on both the enhancement of cancer risk and the efficiency dampening of chemotherapy, immunotherapy and radiotherapy protocols. In this context, it seems quite obvious that the introduction in the clinic of strategies that may allow microbiota modulation may be a key step towards providing an optimum biological framework to facilitate cancer prevention and treatment [154]. The decrease in gastric cancer attained by eradicating H. pylori is a clear example of the anticancer potential of microbiota modulation [155].…”
Section: Central Regulatory Role Of the Microbiotamentioning
confidence: 99%